2012
DOI: 10.1051/0004-6361/201219422
|View full text |Cite
|
Sign up to set email alerts
|

The size, luminosity, and motion of the extreme carbon star IRC+10216 (CW Leonis)

Abstract: Very Large Array observations of the extreme carbon star IRC+10216 at 7 mm wavelength with 40 milli-arcsec resolution resolve the object's radio emission, which forms an almost round uniform disk of 83 milli-arcsec diameter, corresponding to 11 AU (for an assumed distance of 130 pc). We find a brightness temperature of 1630 K for the radio photosphere. Since the emission is optically thick, we can directly estimate IRC+10216's average luminosity, which is 8600 L . This value is in excellent agreement with what… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 45 publications
11
90
2
Order By: Relevance
“…Bakker et al (1997) identified a correlation between C2 column densities and circumstellar expansion velocity. Our results show no correlation between C3 or C5 column densities with the shell velocity; however if the more recent stellar velocity of -26.0 km s −1 (Menten et al 2012) is used for IRC +10216, a slight increase in column density is seen for decreasing shell velocity. Our velocities are consistent and indicate a typical circumstellar shell velocity to be approximately 17.5 km s −1 .…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Bakker et al (1997) identified a correlation between C2 column densities and circumstellar expansion velocity. Our results show no correlation between C3 or C5 column densities with the shell velocity; however if the more recent stellar velocity of -26.0 km s −1 (Menten et al 2012) is used for IRC +10216, a slight increase in column density is seen for decreasing shell velocity. Our velocities are consistent and indicate a typical circumstellar shell velocity to be approximately 17.5 km s −1 .…”
Section: Discussioncontrasting
confidence: 77%
“…This allows a broad variety of molecular species to form from the remaining oxygen-rich or carbon-rich material in circumstellar shells of asymptotic giant branch (AGB) stars (Olofsson 2008). IRC +10216 (CRL 1381) is carbon-rich and is the best studied example of a circumstellar shell (Glassgold 1996;Cernicharo et al 2010;Menten et al 2012) with more than 80 molecules detected so far, typically from pure rotational spectra (Agúndez et al 2012). Approximately 80% of these molecules are carbon containing species (Ziurys 2006), although an interesting oxygen chemistry has also been shown to exist (Agúndez & Cernicharo 2006), thus making circumstellar shells a challenging environment for physical and chemical models (Cherchneff 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This can be naturally explained by central-star occultation, because the estimated maser-region size (1.44R * ) is comparable to the measured diameter (4 R * ) of the radio photosphere of the star (Menten et al 2012). On the other hand, the amplification of the radiation from the central star by the maser system could also contribute.…”
Section: Maser Propertiesmentioning
confidence: 70%
“…25. Menten et al (2012) The position fitted to the zeroth moment of each line apart from 13 CO is within 30 mas (the combined position uncertainties) of the continuum peak; the mean position of all these lines is within 6 mas. The 13 CO peak is offset by (−67, −37) mas, but this is probably due to the relatively poor fit of a Gaussian component to the complex and extended CO emission (see Sect.…”
Section: Astrometrymentioning
confidence: 93%
“…For an effective temperature of 2330 K (De Beck et al 2012), this yields a stellar diameter of 48 mas. Groenewegen et al (1997) reported a stellar diameter of 70.2 mas at 243 GHz for an effective temperature of T eff of 2000 K. Menten et al (2012) found a diameter of 83 mas at 43 GHz. Thus, the star is probably unresolved at our spatial resolution.…”
Section: Stellar and Dust Propertiesmentioning
confidence: 99%